Hadramis, Shimalis and Muwalladin: negotiating cosmopolitan identities between the Swahili Coast and southern Yemen - Walker, I (Routledge, 2008)
Cosmopolitanism refers to the ability of people to negotiate, with varying degrees of effectiveness, between and across different cultures with which they may or may not be familiar. This paper looks at the strategies called into play by individuals of Hadrami descent who return from East Africa to their 'homes' in Hadramawt in southern Yemen only to find that welcomes are ambivalent and that they are neither entirely Hadrami nor entirely foreign. While appearing to belong, through kin links, for example, or religious practice, their identity as 'Swahili' is never entirely shrugged off; instead it constitutes an essential element of their social armoury as they interact with varying degrees of success in what is, often, an alien environment. Choices of strategies for negotiating pathways through various social contexts depend on individuals being inscribed within, or belonging to the culture with which they find themselves confronted; by implication, wider strategies of negotiating through different cultures, as foreign-born Hadramis must do in Africa as well as in Hadramawt, both places to which they have ties, depends on a partial belonging. This partial belonging might otherwise be called cosmopolitanism.